Effect of Mn-doping on the morphological and electrical properties of (Ba0·7Sr0.3) (MnxTi1−x)O3 materials for energy storage application. Issue 18 (15th September 2022) - Shalu, Saumya; Roy, Sunanda; Mukherjee, Anindita; Bal, Trishna; Rout, Sanjeeb Kumar; Dasgupta Ghosh, Barnali
Abstract: Lead-free (Ba0·7 Sr0.3 ) (Mnx Ti1−x )O3 (x = 0.0, 1.0, 2.0, 4.0, 6.0, and 8.0%) ceramics were effectively synthesized by the sol-gel process. XRD and Raman spectroscopy confirm the single-phase perovskite structure with tetragonal symmetry, for all compositions. An in-depth analysis of the chemical composition and thermochemistry of the ceramics was carried out via FT-IR and TG-DTG. Morphological analyses of the samples revealed that doping Mn at higher concentrations suppresses the grain size and grain growth rate. The dielectric properties increased first and then decreased with increasing Mn content. The ferroelectric properties represented similar trend in polarization and energy storage efficiency as showed in dielectric properties. 2% Mn-doped sample exhibits the best dielectric and energy storage performance which is attributed to increased densification and grain size effects. Dielectric anomaly caused by defect dipole polarization was observed in temperature-dependent dielectric constant curves, for 6% and 8% Mn-doped samples. This study is helpful to establish the relationship between the structure, morphology, dielectric and ferroelectric properties of Mn substituted Ba0·7 Sr0·3 TiO3 ceramics.